Experimental Study of the Composition and Structure of Granular Media in the Shear Bands Based on the HHC-Granular Model - Guang-jin Wang; Xiang-yun Kong; Chun-he Yang (Journal of Spectroscopy)
The researchers cannot control the composition and structure of coarse grained soil in the indoor experiment because the granular particles of different size have the characteristics of random distribution and no sorting. Therefore, on the basis of the laboratory tests with the coarse grained soil, the HHC-Granular model, which could simulate the no sorting and random distribution of different size particles in the coarse-grained soil, was developed by use of cellular automata method. Meanwhile, the triaxial numerical simulation experiments of coarse grained soil were finished with the different composition and structure soil, and the variation of shear strength was discussed. The results showed that the internal friction angle was likely to reduce with the increasing of gravel contents in the coarse-grained soil, but the mean internal friction angle significantly increased with the increment of gravel contents. It indicated that the gravel contents of shear bands were the major factor affecting the shear strength.